ANALYSIS OF FACTORS AFFECTING FARMING HOUSEHOLD FOOD SECURITY POST-NATURAL DISASTER IN LAMBARA, CENTRAL SULAWESI - Karlina Muhsin Tondi; Wira Hatmi; Nurmedika Nurmedika (Universitas Tadulako, 2023)
This research aims (1) to discover the factors influencing food security; (2) to determine food security after a natural disaster occurred on September 28, 2018. The research was conducted in Lambara, Central Sulawesi, from June to November 2021. The population of this study was 31 farmer households and, at the same time, became the study's sample. Data were obtained in several ways: literature study, interviews, and questionnaires. Data relating to food security is processed using portion of food expensesanalysis. On the other hand, an analysis of the factors affecting food security is carried out by OLS (Ordinary Least Square) analysis in multiple regression. Testing the hypothesis in multiple linear regression analysis is carried out by testing the regression coefficients, namely testing the regression coefficients as a whole (F-test) and the regression coefficients partially (t-test) with a 2-way test α = 5%. From the data processing results, it is known that the food security of farming households after natural disasters based on the share of food expensesis 70.97% food secure and 29.03% food insecure. Factors with significant effects on food security after natural disasters are income and level of education.